Painting the White House Green : Rationalizing Environmental Policy Inside the Executive Office of the President. - Lutter, Randall (Earthscan, 2004)
Presidents, like kings, lead cloistered lives. Protecting the president from too much isolation are advisers and aides who help ensure that the administration achieves its policy goals while enjoying broad political support. In economics and environmental policy, where disagreement among stakeholders and expert opinion is especially strong, the president needs good advice about political strategy, as well as unbiased information about the substance of policy issues. It is the latter need that the Council of Economic Advisers (CEA) is intended to address. Painting the White House Green collects.